STUDI KASUS TEKNIK PEMERIKSAAN URETROGRAFI DENGAN KLINIS RETENSI URINE DI INSTALASI RADIOLOGI RSUD DR SOESELO KABUPATEN TEGAL - Ditry, Dhara; Mahanani, Ayu; Nadia Putri, Maizza (Penerbit Lafadz Jaya, 2025)
Urethrography is a radiological procedure performed to enhance the imaging quality of the urethra, particularly in cases involving difficulty urinating or urethral injury. This urethrography examination technique utilizes AP and RPO post-contrast projections, with a single introduction of contrast media and the use of a Brodney clamp. At RSUD (Regional General Hospital) dr. Soeselo, Tegal Regency, the same projections are used, but the contrast media is introduced gradually without the use of assistive devices. This study aims to explore the urethrography examination technique applied at the Radiology Installation of RSUD dr. Soeselo, focusing on the gradual introduction of contrast media and the use of a syringe without assistive devices like the Brodney clamp. This research employed a descriptive qualitative approach with a case study design. Data collection took place at RSUD dr. Soeselo, Tegal Regency, from August 2024 to March 2025. The subjects of the study included one radiology specialist and three radiographers. The object of the research was the urethrography technique in cases of urinary retention. Data were collected through observations, interviews, and documentation. Data analysis involved data reduction, data presentation, and conclusion drawing. Observations and interviews indicated that at RSUD dr. Soeselo, the examination technique was performed using two projections: plain AP pelvis and RPO post-contrast. The introduction of contrast media was conducted gradually to ensure that the contrast media properly entered the urinary bladder (VU), and no assistive devices like the Brodney clamp were used due to their unavailability at the hospital. Instead, a modified 20cc syringe with hypafix was utilized. The urethrography examination at the Radiology Installation of RSUD dr. Soeselo, Tegal Regency, was conducted using AP projection for plain pelvis imaging and RPO post-contrast. The contrast media was introduced gradually through the penile opening to ensure that the contrast reached the urethra and urinary bladder. Due to the lack of assistive devices like the Brodney clamp, a modified 20cc syringe with hypafix was used as a substitute.